(untitled) (BIRDEM Medical Journal, 2014)
Infertility has been classified with respect to a number of parameters; prominent amongst which are time, causes, treatment cost and socio-cultural implications. The most widely accepted practical classification distinguishes between primary and secondary infertilities with a further sub classification into 3 clearly defined groups that include ovulatory dysfunction, fallopian tube compromise and male factor alongside an ambiguous and controversial group labeled as unexplained infertility. In infertility work-up various procedures can be carried out in isolation or in different combination, depending on the indication. Other complimentary procedures can be done when specifically required. So, with infertility in general the diagnosis of tubal infertility should be tailored to the individual patient. Here is a review on an evidence based approach to diagnose the tubal factors for infertility. Purpose of review: The investigation for potential tubal disease is an essential step in the work-up of infertility. This review article will provide an overview of evidence based diagnosis of tubal factor infertility. The different diagnostic tools will be described together with discussion of different minimal access surgical approaches. We intend to highlight the capital and central role of minimal access procedures playing in the diagnosis of tubal infertility as well as to demonstrate the positive impact it has in the fight against infertility; thus redefining the classification and pathology. DOI: http://dx.doi.org/10.3329/birdem.v4i1.18551 Birdem Med J 2014; 4(1): 33-37